2017
DOI: 10.1016/j.jfma.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin alleviates cardiomyocyte apoptosis by suppressing TRB3 induced by acute myocardial infarction and hypoxia

Abstract: Background/Purpose: TRB3 (tribbles 3), an apoptosis-regulated gene, increases during endoplasmic reticulum stress. Hypoxia can induce inflammatory mediators and apoptosis in cardiomyocytes. However, the expression of TRB3 in cardiomyocyte apoptosis under hypoxia is not thoroughly known. We investigated the regulation mechanism of TRB3 expression and apoptosis induced by hypoxia in cardiomyocytes. Methods: An in vivo model of acute myocardial infarction (AMI) was applied in adult Wistar rats to induce myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…TRIB3 is a stress-related gene that induces apoptosis during ER stress [46]. In the heart, TRIB3 has a low expression but is induced by hypoxia [47] or the transcription factor NF-kappaB, which it negatively regulates. In addition, TRIB3 sensitizes cells to TNF-and TRAIL-induced apoptosis and is involved in insulin signaling [48].…”
Section: Discussionmentioning
confidence: 99%
“…TRIB3 is a stress-related gene that induces apoptosis during ER stress [46]. In the heart, TRIB3 has a low expression but is induced by hypoxia [47] or the transcription factor NF-kappaB, which it negatively regulates. In addition, TRIB3 sensitizes cells to TNF-and TRAIL-induced apoptosis and is involved in insulin signaling [48].…”
Section: Discussionmentioning
confidence: 99%
“…chen et al (28) reported a protective role of FGd5-aS1 in lipopolysaccharide-induced inflammatory injury in human periodontal ligament cells, as evidenced by counteraction of cell apoptosis and pro-inflammatory cytokine secretion via the nF-κB pathway. The role of FGD5-AS1 in inflammation in AMI requires further investigation, although ischemia-hypoxia is known to highly induce an inflammatory response in AMI (29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that inhibition of apoptosis is an effective method to prevent myocardial infarction. Statins can reduce cardiomyocyte apoptosis by reducing the expression of TNF-α, and TRB3 in myocardial cells, inhibit ventricular remodeling after AMI, and improve cardiac function [4,[31][32] . In this study, the radioactive concentration signal of the 99m Tc-duramycin imaging in the statin treatment group was lower than that in the corresponding AMI group by visual analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are hydroxymethylglutaric acid coenzyme reductase inhibitors, which have a significant lipid-lowering effect in the treatment of cardiovascular disease. Numerous studies showed that statins could effectively prevent apoptosis of myocardial cells in the infarcted area, reduce wall tension during diastole and reperfusion injury and myocardial ischemia, which may mechanistically attenuate myocardial apoptosis [2][3][4] . Therefore, it is pivotal that how to monitor myocardial cell death during myocardial infarction in vivo and evaluate the effects of statins and other anti-apoptotic drugs on myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%